Islamic fasting leads to an increased abundance of Akkermansia muciniphila and Bacteroides fragilis group: A preliminary study on intermittent fasting - Özkul, Ceren; Yalınay, Meltem; Karakan, Tarkan (Turkish Journal of Gastroenterology, 2019)
Background/Aims: It has been largely accepted that dietary habits affect intestinal microbiota composition. In this pilot study, we hypothesized that time-restricted feeding, which can be regarded as a type of intermittent fasting, may have a distinct effect on intestinal microbiota. Ramadan fasting is an excellent model to understand how time-restricted feeding affect the microbiota. Materials and Methods: A total of nine subjects were included in this study during Ramadan, consisting of 17 h of fasting/day during a 29-day period. Stool samples were collected at baseline and the day of the end of Ramadan. 16S rRNA qPCR assay has been performed for quantification of Akkermansia muciniphila, Faecalibacterium prausnitzii, Bifidobacterium spp., Lactobacillus spp., Bacteroides fragilis group, and Enterobacteriaceae. Blood samples were also collected to test for metabolic and nutritional parameters.Results: A significantly increased abundance of A. muciniphila and B. fragilis group was observed in all subjects after Islamic fasting when compared with the baseline levels (p=0.004 and 0.008, respectively). Serum fasting glucose and total cholesterol levels were also significantly reduced in all of the subjects (p<0.01 and p=0.009, respectively).Conclusion: Islamic fasting, which represents intermittent fasting, leads to an increase in A. muciniphila and B. fragilis group, which were considered as healthy gut microbiota members. Although this is a pilot study, which should be tested with larger sample size, there are a very limited number of studies in the literature on fasting and microbiota in human subjects. Thus, our present findings may contribute to the understanding of fasting-gut microbiota interaction.